Process Evaluation of a National Elderly Nutrition–Care Program in Iran: Perspectives of Clients and Providers - Foroumandi E; Alizadeh M; Khodayari-Zarnaq R; Kheirouri S (Dove Medical Press, 2020)
Elaheh Foroumandi,1,2 Mohammad Alizadeh,1 Rahim Khodayari-Zarnaq,3 Sorayya Kheirouri1 1Nutrition Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 2Students’ Research Committee, Tabriz University of Medical Sciences, Tabriz, Iran; 3Iranian Center of Excellence in Health Management, School of Management and Medical Informatics, Tabriz University of Medical Sciences, Tabriz, IranCorrespondence: Sorayya KheirouriDepartment of Nutrition, Faculty of Nutrition, Tabriz University of Medical Sciences, Attar Nishabouri Street, POBOX: 14711, Tabriz 5166614711, I. R. IranTel +98-41-33362117Fax +98-41-33340634Email sorayya1376@gmail.comObjective: As aging populations increase, many countries have begun implementation of policies to improve elder health and nutrition. This study evaluated key process components of nutrition sections of a national elderly integrated–care program in health-care centers in Iran.Methods: With stratified three-stage random cluster sampling, a total of 256 elderly subjects (clients) and 76 staff members of health-care centers (providers) participated in the study. Quantitative and qualitative data were collected using two self-administrated questionnaires to evaluate various components of process evaluation for clients and providers. Program reach was measured by the ratio of the number in the target group who underwent the program to the number of eligible individuals. Exposure rate was measured as clients’ awareness of program services. Delivery and fidelity were assessed from providers’ reports for each service. Satisfaction rates were assessed for the whole program and for each service of the program. All reasons behind strengths and weaknesses in each of the process-evaluation components were examined and are reported in detail.Results: The clients reported low-reach (20.0%) and moderate-exposure rates of 77.5%, with a program target of 90%. Primary training sessions were delivered to the providers as intended (100%), but most planned services for clients, especially vitamin and mineral supplementation, follow-up, and physical activity sessions, were poorly implemented, as they were delivered correctly to 24.7% (n=63, vitamin and mineral supplementation), 24% (n=62, follow-up), and 40.3% (n=103, physical activity sessions) of the clients, with a set program goal of 60%. An overall low level of implementation fidelity was observed, and 39.3% (n=30) of the providers believed that most clients did not benefit from the nutritional services. Overall, less than half (42.8%, n=101) the clients were highly satisfied with the program.Conclusion: The process evaluation showed insufficient reach, exposure, and fidelity of the program, as well as imprecise delivery of some services, which resulted in low levels of client satisfaction. The findings may have implications for further reinforcement of the program, and indicate the importance of continuous monitoring and evaluation of such programs.Keywords: process evaluation, elder, nutrition, elderly integrated–care program, national, Iran